ANALISIS KEBUTUHAN ARSITEKTUR DAN DESAIN ANTARMUKA SISTEM MANAJEMEN RISIKO BERBASIS PENELITIAN HAOUSE OF RISK PADA INSTITUSI PENDIDIKAN - Intan Dzikria; Nabila Amanda Maharani (Jurnal Teknik Informatika dan Komputer, 2024)
Risk management in educational institutions plays an important role because the educational environment will always change and become increasingly complex. Risk management can provide support to educational institutions to identify, assess and manage risks in a systematic and structured way. House of Risk (HOR) is an approach used to manage risk and focuses on formulating preventive actions and handling the causes of risk, by combining FMEA and HOQ principles. This research aims to design an architectural requirements analysis and risk management system interface design using the design thinking stages. This research produces an architectural design, software requirements, and interface design for a higher education risk management system. The user interface design was tested using usability testing with a score of 87.5, which shows that the interface design is useful for various system actors. The results of this research can be a reference for further research in implementing the creation of a HOR-based risk management system in web-based educational institutions.